Chess and learning in the area of mathematics in second cycle students, General Studies, Universidad San Martín de Porres, 2019 - Chanca Cortéz , Luis (2021)
This pre-experimental study aimed to analyze the influence of the game of chess and learning in the area of mathematics in university students, thinking about this purpose, the pre and post test was applied to a sample of 40 second-year students from the Professional School of Administration. Faculty of Economic and Financial Accounting Sciences of the San Martin de Porres University, 2019, whose information collected was processed with the SPSS program, which allowed the application of the T Student difference test of means for independent samples. The results explain that the general hypothesis verified the influence of chess on the academic performance of the Mathematics Area, since there is a difference of 1.76 points between the control and experimental groups. In the specific hypotheses, they also confirmed the influence of chess on learning linear equations, the derivative of a function, the application of the derivative and the Integral Calculus, since their mean differences between both groups are 0.49 points, 0.47 points, 1.47 points and 1.95 points, respectively. Therefore, it concluded that this activity positively influences mathematical learning and its dimensions, linear equations, derivative of a function, application of the derivative and integral calculus.